2018
DOI: 10.1080/13685538.2018.1466876
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous testosterone does not improve prediction of incident cardiovascular disease in a community-based cohort of adult men: results from the Tehran Lipid and Glucose Study

Abstract: Testosterone could not add to the predictive value of FRS for CVD in men, either directly, or through interactions with FRS variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…30 Among these, FRS and PCE are frequently used. 6,30,31 Nevertheless, nowadays, efforts have been made to introduce more comprehensive CVD risk predictive assessment tools by adding biochemical and imaging parameters, to previous traditional ones, such as coronary artery calcification, 4,9,32 carotid intima-media thickness, 33 ankle-brachial index, brachial flow-mediated dilation, high-sensitivity C-reactive protein, family history of CHD, 4 microalbuminuria, chronic kidney disease, 34 and hemoglobin A1C. 11 For instance, data from the Rotterdam study on 2,153 asymptomatic participants showed that, for the outcome CHD, the C statistic improved from 0.693 for the FRS refitted model to 0.743, 0.740, and 0.749 by the addition of coronary, aortic arch, and carotid calcium, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…30 Among these, FRS and PCE are frequently used. 6,30,31 Nevertheless, nowadays, efforts have been made to introduce more comprehensive CVD risk predictive assessment tools by adding biochemical and imaging parameters, to previous traditional ones, such as coronary artery calcification, 4,9,32 carotid intima-media thickness, 33 ankle-brachial index, brachial flow-mediated dilation, high-sensitivity C-reactive protein, family history of CHD, 4 microalbuminuria, chronic kidney disease, 34 and hemoglobin A1C. 11 For instance, data from the Rotterdam study on 2,153 asymptomatic participants showed that, for the outcome CHD, the C statistic improved from 0.693 for the FRS refitted model to 0.743, 0.740, and 0.749 by the addition of coronary, aortic arch, and carotid calcium, respectively.…”
Section: Discussionmentioning
confidence: 99%